KEGIATAN PENYEDIAAN JASA CALO KARTU PRAKERJA DITINJAU DARI FATWA DSN MUI NOMOR 114/DSN-MUI/IX/2017 TENTANG AKAD SYIRKAH DI KOTA MEDAN - Aulia Fitriyanti; Tetty Marlina Tarigan (LPPM Universitas Ekasakti Padang, 2023)
The purpose of this study was to examine the Provision of Pre-Employment Card Brokerage Services in terms of DSN MUI Fatwa Number 114/DSN-MUI/IX/2017 Concerning the Study of Syirkah Contracts in the Medan City Case. The research method used is qualitative with an empirical approach with two data sources used, namely primary data interviews with 5 pre-employment program beneficiary informants and 2 pre-employment program jockey informants and secondary data in the form of books, articles related to material and DSN MUI Fatwa Number 114/ DSN-MUI/IX/2017. From the results of the research that the researchers have done on the Activities of Provision of Pre-Employment Card Brokerage Services In terms of DSN MUI Fatwa Number 114/DSN-MUI/IX/2017 Concerning Syirkah Contracts Case Study of Medan City, both in the field and legally it is known that the activities of pre-employment jockey service providers include syirkah contracts that are permitted in the form of Syirkah 'abdan/syirkah a'mal, namely contracts carried out in collaboration with services or expertise which are transferred to another person based on agreement or proportion, one example of this pre-employment jockey.